The relationship between personality dimensions, spirituality, coping strategies and clinical clerkship satisfaction among intern nursing students: a cross-sectional study - Yasser Rezapour-Mirsaleh; Mahdi Aghabagheri (BMC, 2020)
Abstract Background The clinical clerkship is a crucial stage in nursing training, yet a dissatisfaction at this stage may cause a nurse to quit in future. This study aimed to investigate the relationship among personality dimensions, spirituality, coping strategies and clinical clerkship satisfaction among intern nursing students. Methods This was a correlational, cross-sectional study. A total of 293 Iranian nursing students, who were fulfilling their clinical clerkship at university-affiliated hospitals in Tehran, were selected using cluster random sampling. All participants were provided with standard questionnaires including personality dimensions (NEO_FFI), spirituality, coping strategies (WoCQ), and satisfaction with clinical clerkship. Data were analyzed using Pearson correlation and hierarchical multiple regression. Results The results showed that spirituality (β = 0.32, p < 0.001), problem-focused coping (β = 0.26, p < 0.001) and extraversion (of personality dimensions, β = 0.22, p < 0.001) played significant roles in predicting clinical clerkship satisfaction among intern nursing students. Regression analysis showed openness (β = 0.14, p < 0.01), extraversion (β = 0.16, p < 0.01), and spirituality (β = 0.23, p < 0.001) could significantly predict problem-focused coping style among intern nursing students. However, personality dimensions and spirituality were not good predictors for emotion-focused coping among these students (p > 0.05). Conclusion Personality dimensions, coping strategies and, in particular, spirituality are good predictors of clinical clerkship satisfaction among intern nursing students. Therefore, paying attention to spiritual needs in nursing students, improving their problem solving skills in dealing with clinical stress and training extraversion characteristics can be effective in enhancing their satisfaction with clinical clerkship.